2006
DOI: 10.1002/elps.200500700
|View full text |Cite
|
Sign up to set email alerts
|

In‐capillary solid‐phase extraction–capillary electrophoresis for the determination of chlorophenols in water

Abstract: A novel CE method combined with SPE in a single capillary was developed for analysis of chlorophenols in water. A frit of 0.5 mm was first made by a sol-gel method, followed by packing a SPE sorbent in the inlet end of the capillary. Two phenol derivatives, 2,4-dichlorophenol and 2,4,5-trichlorophenol, were used as the model compounds. By loading sample solutions into the capillary, the two chlorophenols were extracted into the sorbent. They were desorbed by injecting only about 4 nL of methanol. Finally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 55 publications
(55 reference statements)
0
29
0
Order By: Relevance
“…As outlined in Section 3, several studies using CE to analyze phenolic compounds in environmental matrices focused primarily on the improvement of sensitivity and sample clean-up techniques [34,68,69,72]. A number of studies reported the use of microchip CE for the determination of phenols [36,38,42,46].…”
Section: Phenolsmentioning
confidence: 99%
See 2 more Smart Citations
“…As outlined in Section 3, several studies using CE to analyze phenolic compounds in environmental matrices focused primarily on the improvement of sensitivity and sample clean-up techniques [34,68,69,72]. A number of studies reported the use of microchip CE for the determination of phenols [36,38,42,46].…”
Section: Phenolsmentioning
confidence: 99%
“…CE remains an important area of investigation for the analysis of these pollutants [34,36,38,39,42,46,61,68,69,72,82,87]. As outlined in Section 3, several studies using CE to analyze phenolic compounds in environmental matrices focused primarily on the improvement of sensitivity and sample clean-up techniques [34,68,69,72].…”
Section: Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b) [44,[49][50][51][52][53][54], or the preconcentrator is inside the separation capillary (Fig. 4c) [55][56][57][58][59][60][61][62][63][64][65][66]. The first inline SPE-CE system with a packed SPE bed was introduced by Guzman et al [49].…”
Section: Packed Bed Spementioning
confidence: 99%
“…In fact, complete system integration for unattended extraction, separation and detection is now possible. The SPE-CE coupling has been used in combination with three different types of treatments, namely: (i) batch procedures [4,5]; (ii) automatic procedures, which usually involve on-line [6,7] or at-line coupling of a flow system to CE equipment [7][8][9][10]; (iii) and procedures performed within the capillary (on-capillary preconcentration) [11][12][13]. The latter two are especially interesting for routine laboratories as they simplify the analyst's work and reduce errors due to human intervention.…”
Section: Introductionmentioning
confidence: 99%